An introduction to internet-based financial investigation: structuring and resourcing the search for hidden assets and information - Goetz, Kimberly (Gower, 2010)
Introduction : why and where to start -- Before you start : ethical considerations -- Thinking about financial fraud and investigations -- What can you do with money? -- Legal structures -- Legal documents -- Starting the search -- Real estate records -- Search engines and web portals -- Government and law related web sites -- Commercial and business-related web sites -- Web sites from non-profits and other organizations -- Additional web sites and resources -- Requesting additional information and understanding what you receive -- Getting help from the numbers -- Dealing with people problems -- Telling the story -- Final thoughts and considerations